Construction, Validation, and Standardization of the Sexual‐DSMapp Application. Issue 2 (16th October 2020) - Delcea, Cristian
Abstract : Objective: The aim of this research was to construct, validate, and standardize a new tool for assessing sexual dysfunction. The Sexual‐DSMapp is an application that can be used on a computer, tablet, or mobile phone. Methods: Of the participants (N=800), 400 met DSM‐5 criteria for clinical dysfunction (the clinical group), and 400 had no dysfunction (the healthy control group). Both groups were 50% male and 50% female. Patients in the clinical group had sexual disorders such as premature ejaculation, erectile dysfunction, diminished sexual desire, orgasm issues, arousal issues, and dyspareunia but no mental, personality, medical, and/or substance use disorders. Average age for both groups was 34, and the average education level was 11.5 years. Participants were from various localities in Romania and were of differing racial‐ethnic groups. Results: Fidelity of the app's nine scales on Cronbach's alpha (0.975), Spearman's rank‐order correlation coefficient (0.986), and the Guttman scale (0.969) reached maximum threshold, was significant on test‐retest reliability, and reached a Cronbach's alpha average of 0.89 for the whole questionnaire. For the test scales, results from 0.76 to 0.98 were obtained, and significant correlation was shown with other questionnaires. The result of the Kaiser‐Meyer‐ Olkin test for adequate participant sampling was 0.939. Analysis of variance indicated significance (p<0.001). Correlation with similar questionnaires showed significant validity. Conclusions: The results of this research suggest that the Sexual‐DSMapp can discriminate between clinical and nonclinical sexual dysfunction and can be used to test and evaluate sexual dysfunctions. HIGHLIGHTS: The Sexual‐DSMapp is a new tool for assessing sexual dysfunction that can be used on a computer, tablet, or mobile phone. The app can discriminate between clinical and nonclinical sexual dysfunction and can test and evaluate sexual dysfunctions. A standardized tool to assess and test for sexual dysfunction will aid advanced technology users, such as specialists in the field of sexology, or patients with sexual dysfunctions.